An Evaluation of Caregiver Strain Experienced by Family Members Living with the Elderly in Selected Villages of Tapi, Gujarat (International Journal of Nursing Education, 2022)
Background: Caregiver strain or burden is a strain experienced by a person who is taking care ofa disabled or chronically ill, and an old age person in the family. Caregivers experience burdens inemotional, physical, psychological, economical, and social aspects of their day-to-day life. Objectives:The objective of the study was to identify and compare caregiver strain experienced by them in physical,physiological, social, emotional, and economic areas and to find the association of caregiver strain withselected demographic variables. Methods: Using convenience sampling technique 247 caregivers wererecruited in the selected villages of Tapi District, Gujarat. And after obtaining their consent caregiverswere interviewed using the caregiver strain index by Robinson BC. Results: 52% of the samples hadmild levels of strain, 40% moderate levels, and eight percent of them with severe levels of strain. Theeconomic strain was the highest (54%) and the physiological strain was the least (13%). Relationshipwith elderly and ability of an elder person to perform Activities of Daily Living had an influenceon caregiver strain. Conclusion: Caregiver burden and its impact need to be explored in detail andmeasures need to be taken to reduce their burden in physical, economical, and emotional areas.
Keywords: Evaluation, Caregiver strain, elderly